(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the physicochemical, microbiological and sensory characteristics of homemade breads with the addition of smoked tilapia shavings (cut in “V” fillet). The shavings were subjected to a smoking process with the addition of aromatic herb extract. 0%, 3%, 6% and 9% of smoked chips in homemade bread were included, being evaluated for proximate, microbiological and sensory composition. All parameters evaluated in the proximate composition showed a significant difference (P<0.05). A quadratic equation for moisture, crude protein, lipids and caloric content was observed, where breads with 3% inclusion of fish meal had lower moisture and protein averages, but higher lipid and caloric value averages. Breads with 9% fishmeal inclusion had higher protein content and lower lipid content. A linear increase in ash content was observed, as fish meal levels increased. Microbiological analysis showed that all homemade breads were within the standards required by legislation, therefore suitable for consumption. The sensory analysis indicated a good acceptance of the product by the tasters, demonstrating the viability of using up to 6% of smoked fish trimming flour inclusion without harming the organoleptic properties. Therefore, it is concluded that the inclusion of 6% of Nile tilapia smoked shavings flour is viable to increase the nutritional value of homemade breads, with this product having excellent sensory acceptance.